PENGARUH MEDIA LEGO HURUF DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ASIYIYAH 5 PADANG - Wafiq Aziza; Yul Syofriend; Elise Muryanti; vivi anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem of children's low reading skills at Kindergarten Aisyiyah 5 Padang sparked this study. This occurs because children's reading development programs that utilize media are uninteresting. way that teaching reading becomes tedious for children quickly. Finding out how much of an impact Lego letter media has on the reading abilities of 5- and 6-year-olds in Kindergarten Aisyiyah 5 Padang is the primary goal of this study. This study employs a quantitative approach and employs a quasi-experimental research method. The children enrolled in Kindergarten Aisyiyah 5 Padang made up the entire population, while fourteen students from classes B4 and B6 made up the sample. Statistical tests for homogeneity, hypothesis testing, and normalcy were applied to the collected data. A sig value of 0.008 was retrieved from the hypothesis test table's sig.(2-tailed) column. Indicating that 0.008 < 0.05, this number is presented. As per the measurement requirements outlined in the hypothesis test, a sig value less than 0.05 is considered significant. Children at Aisyiyah Kindergarten 5 Padang, who are five or six years old, benefit from using Lego letter media to hone their reading abilities.